Effect of Cardiac Respiratory Fitness Exercises (CRF) According to Some Biomechanical Laws in P02 and Lung Efficiency of Female Students - Alkhalidi, Dr. Mohammed Jasim Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The research focused on the impact of cardio-respiratory fitness exercises according to some biomechanical laws in PO2 and lung efficiency (VC, FEV1/ FVC) for female students. And try to reach the best development of the variables, as the use of different aids such as ropes, terraces and ladders to help students to perform the required exercises. The experimental group was trained in cardio-respiratory fitness exercises. These exercises were organized according to some biomechanical laws during a semester period for the fourth preparatory students and for 25 weeks at the rate of two training units per week. The control group, where the statistical results showed the superiority of the experimental group over the control group.